2005
DOI: 10.1081/fst-120027201
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene C60 Complexed with Poly(N-Vinyl-pyrrolidone) (C60/PVP) Prevents the Disturbance of Long-Term Memory Consolidation Induced by Cycloheximide

Abstract: It is shown that fullerene C 60 /water-soluble complex with PVP molecular mass of 10,000 injected in the dorsal hippocampus completely prevents the development of amnesia caused by cycloheximide, the inhibitor of protein synthesis. With the increased PVP molecular mass up to 25,000 the complex does not produce protective effect disturbance of learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Moreover, unique photo-physical, photo-chemical, and tribological properties in C 60 and derivatives are implemented widely in various fields such as catalysis (1,2), lubrications (1,3), solar cells (4,5), and biomedicals (6)(7)(8)(9)(10)(11). As C 60 is spherical in shape, small in size, and has capability to generate reactive oxygen species, such as superoxide anion radical (O 2 -• ) and hydroxyl radical ( .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, unique photo-physical, photo-chemical, and tribological properties in C 60 and derivatives are implemented widely in various fields such as catalysis (1,2), lubrications (1,3), solar cells (4,5), and biomedicals (6)(7)(8)(9)(10)(11). As C 60 is spherical in shape, small in size, and has capability to generate reactive oxygen species, such as superoxide anion radical (O 2 -• ) and hydroxyl radical ( .…”
Section: Introductionmentioning
confidence: 99%
“…As C 60 is spherical in shape, small in size, and has capability to generate reactive oxygen species, such as superoxide anion radical (O 2 -• ) and hydroxyl radical ( . OH) under photoirradiation (8)(9)(10)(11)(12), it holds high potential in biological and medical applications. In general, C 60 and its derivatives exhibit two important biologically relevant features necessary for medicinal applications: (i) great ability to quench free radicals and (ii) formation of highly reactive singlet oxygen via long-lived triplet excited state in the presence of oxygen upon UV or visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was shown that microinjections of complexes of С 60 and poly-N-vinylpyrrolidine (С 60 PVP) into the rat hippocampus prevent the development of amnesia induced by suppression of biosynthesis of proteins [12]. Recently, it was found that С 60 HyFn inhibit aggregation of amyloid Аβ peptide under conditions of a model of Alzheimer's disease in mice [13].…”
Section: Introductionmentioning
confidence: 99%
“…A) Immunoblotting of the proteins of intermediate filaments obtained from control animals (1-4), rats under conditions of chronic alcoholization(5-7), animals that consumed С 60 FWS(8)(9)(10), and rats that consumed combined solutions of ethanol and С 60 FWS(11)(12)(13). B) Averaged results of the quantitative measurement of GFAP obtained by scanning of polypeptide zones and their computer processing after immunoblotting.…”
mentioning
confidence: 99%